Development of Visual Systems for Faces and Objects: Further Evidence for Prolonged Development of the Face System - Meinhardt-Injac, Bozana; Persike, Malte; Meinhardt, Günter (PloS one, 2014)
The development of face and object processing has attracted much attention; however, studies that directly compare processing of both visual categories across age are rare. In the present study, we compared the developmental trajectories of face and object processing in younger children (8-10 years), older children (11-13 years), adolescents (14-16 years), and adults (20-37). We used a congruency paradigm in which subjects compared the internal features of two stimuli, while the (unattended) external features either agreed or disagreed independent of the identity of the internal features. We found a continuous increase in matching accuracy for faces and watches across childhood and adolescence, with different magnitudes for both visual categories. In watch perception, adult levels were reached at the age of 14-16, but not in face perception. The effect of context and inversion, as measures of holistic and configural processing, were clearly restricted to faces in all age groups. This finding suggests that different mechanisms are involved in face and object perception at any age tested. Moreover, the modulation of context and inversion effects by exposure duration was strongly age-dependent, with the strongest age-related differences found for brief timings below 140 ms. The results of the present study suggest prolonged development of face-specific processing up to young adulthood. The improvement in face processing is qualitatively different from the improvement of general perceptual and cognitive ability.